Case Report: The Monogenic Familial Steroid-Resistant Nephrotic Syndrome Caused by a Novel Missense Mutation of NPHS2 Gene A593C in a Chinese Family - Bai, Ling; Zhuang, Jing; Zhang, Changrong; Lu, Chen; Tian, Xuefei; Jiang, Hong (Frontiers in Pediatrics, 2021)
Background: Pathogenic variants in the NPHS2 gene encoding podocin in kidney podocyte are associated with autosomal recessive steroid-resistant nephrotic syndrome (SRNS) by disrupting podocyte function and the integrity of the glomerular filtration barrier. The outcome is generally poor by progressing into the end-stage renal disease (ESRD). With the help of gene diagnostics, we can further understand the role of podocin of podocytes in the development and progression of SRNS. However, the pathological mutation of NPHS2 and clinical relevance remain further elusive. Case Presentation: Two siblings, a 15-year-old girl and her 10-year-old younger brother from a consanguineous Chinese family, presented with nephrotic syndrome. Both of them developed progressive proteinuria starting from the 5-year-old of age. The renal pathological lesions for them revealed focal segmental glomerulosclerosis (FSGS). There was no response to the glucocorticoid, calcineurin inhibitors, and rituximab treatment. The female affected patient received the hemodialysis treatment due to ESRD in June 2020; the male patient was still in follow-up presenting with SRNS. The mutational screening of the two patients and their parents using Trio whole-exome sequencing showed the NPHS2 gene de novo mutation in exon 5 (A593C), for which the two siblings were homozygous and their parents confirmed heterozygous asymptomatic carriers. No other SRNS-related gene variants with the SRNS were determined. Conclusion: Pathological gene variants screening in children clinically suspected with SRNS might be helpful in the diagnosis as well as appropriate decisions on treatment strategies and prediction of prognosis.